MANAGING IT: DOES AGILE SOFTWARE DEVELOPMENT SOLVE BUYER NEEDS? - Brown, John; Conrade, Lloyd; Callender, Guy (The journal of contemporary issues in business and government, 2009)
A variety of innovations in software development practices, referred to by the collective term agile, have arisen in recent years partly as an attempt to deal with the considerable amount of complexity inherent in many software development projects. These agile approaches to software development are increasingly gaining acceptance with suppliers of software development services. Agile, in its various forms, appears to be a range of supplier responses to a set of problems traditionally incurred in contracted software development projects. Yet the extent to which the needs of the public sector (as one category of procurer) are faced is more questionable. Are the needs of a public sector procurer really satisfied with agile methods and practices as the framework for software development? Is agile really the solution to the original problem set?